UMP signed MoU with New Advanced Technology Sdn.Bhd. (NATECH) - Muhammad Hafiz Aswad, Ahmad Kamal (Penerbit UMP, 2013)
Kuala Lumpur- Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) and exchanged the document with New Advanced Technology Sdn.Bhd. (NATECH).